(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In the dynamic landscape of today’s business environment, advertising campaigns play a pivotal role in shaping and influencing consumer behavior. This abstract explores the multifaceted ways in which advertising strategies are employed to connect with target audiences, create brand awareness, and ultimately drive consumer decision-making. Drawing upon a comprehensive review of relevant literature and case studies, this research sheds light on the various psychological and emotional triggers embedded in effective advertising, elucidating the mechanisms by which campaigns leave a lasting impact on consumer perceptions. The study delves into the evolving nature of advertising in the digital age, emphasizing the significance of online platforms, social media, and interactive content in capturing the attention of modern consumers.